Predictors of gestational weight gain in western India: Findings from a longitudinal study across rural and urban cohorts - Mugdha Deshpande; Neha Kajale; Nikhil Shah; Ketan Gondhalekar; Vivek Patwardhan; Anagha Pai Raiturker; Sanjay Gupte; Leena Patankar; Jasmin Bhawra; Anuradha Khadilkar; Tarun Reddy Katapally (PLoS ONE, 2025)
Background Gestational weight gain-GWG is an important predictor of neonatal growth. However, there is dearth of literature from rural and urban India depicting longitudinal patterns and determinants of GWG. To address this gap, our objectives were to study longitudinal patterns and predictors of GWG in pregnant women residing in rural and urban areas in and around Pune city, Maharashtra, India and to compare them with pre-existing guidelines provided by IOM, 2009. Methods This study enrolled 268(134-rural and 134-urban) healthy singleton pregnant women attending antenatal care centers in and around Pune, India between August 2020-September 2023. Participants were measured for anthropometry and interviewed for socioeconomic status, diet, physical activity, sleep quality, and prenatal distress once in each trimester. Pre-gestational weight status was calculated using WHO, Asian-Pacific, and South Asian BMI cut-points. GWG was estimated using IOM, 2009 guidelines. Findings The observed mean GWG was 10.9 ± 4.2 kg(rural:9.9 ± 3.7, urban:11.9 ± 4.5). 61.2% of rural and 30% of urban underweight pregnant women did not gain adequate weight. 11.8% of rural and 57.3% of urban pregnant women with overweight or obese BMI exceeded recommended guideliness. Key predictors of inadequate GWG in second and third trimesters were low socio-economic status, parity, underweight pre-gestational BMI, prenatal distress, and poor sleep. The primary predictor of excessive GWG was overweight or obese pre-gestational BMI. These findings were consistent across all BMI classifications. Conclusion Our findings indicate that urban underweight pregnant women gained significantly higher weight. There was health disparity between rural and urban pregnant women that needs to be addressed to improve health of pregnant women. We have identified important modifiable factors such as dietary intake, physical activity, etc. to ensure optimal GWG which can inform public health policies. Further research is needed to assess whether context-specific GWG recommendations would be beneficial as our study is based on single geographical location and timeframe.